2008
DOI: 10.1001/archpedi.162.7.642
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Posttraumatic Stress and Depressive Symptoms and Functional Outcomes in Adolescents Followed Up Longitudinally After Injury Hospitalization

Abstract: Early PTSD and depressive symptoms are associated with a broad spectrum of adolescent functional impairment during the year after physical injury. Coordinated investigative and policy efforts that refine mental health screening and intervention procedures have the potential to improve the functioning and well-being of injured youth treated in the acute care medical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 42 publications
8
134
0
Order By: Relevance
“…Previous research has shown that PTSD has a substantial impact on health-related quality of life (HRQoL), of adult hospitalized injury patients as was demonstrated by Holbrook et al in one of the few studies that addressed this matter [1,9]. Similar results were found among adolescents and children [10,11]. However, these studies were again restricted to victims at the higher end of the severity spectrum.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous research has shown that PTSD has a substantial impact on health-related quality of life (HRQoL), of adult hospitalized injury patients as was demonstrated by Holbrook et al in one of the few studies that addressed this matter [1,9]. Similar results were found among adolescents and children [10,11]. However, these studies were again restricted to victims at the higher end of the severity spectrum.…”
Section: Introductionmentioning
confidence: 66%
“…A study of patients with PTSD following cardiac arrest reported similar findings [27]. In another study among adolescent victims PTSD was associated with impairments in Role/Social Behavioral, Role/Social Physical, Bodily Pain, General Behavior, Mental Health, and General Health Perceptions subscales of the 87-item Child Health Questionnaire [11]. The resulting EQ-5D summary scores of injury patients with PTSD found in the current study are approximately in the range of: the utility scores that Holbrook et al derived with the Quality of Wellbeing scale [9].…”
Section: J Depress Anxietymentioning
confidence: 78%
“…Children who incur an injury are at risk for developing post-traumatic stress disorder (PTSD) [2][3][4]. The severity of a child's injury does not predict PTSD [5,6], which can make it difficult for medical professionals to determine when a child will develop psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Automated screening for PTSD using known risk factors and characteristics of the index injury is also feasible. 20,38 In adolescents, PTSD is associated with a broad spectrum of functional impairments across multiple domains. 20 Although stepped care interventions for the prevention and treatment of PTSD in injured adults have been effective, 39,40 initial interventions for the prevention of acute stress symptoms and PTSD in children and adolescents have not been shown to be effective 41 and additional clinical trials are clearly needed.…”
Section: Discussionmentioning
confidence: 99%